Pharmacological approaches towards rationalizing the use of endoparasitic drugs in small animals - Sanchez Bruni, Sergio Fabian (2006)
Parasitic diseases are an important health concern to small animal veterinarians worldwide, and their zoonotic potential is also of relevance to human medicine. The treatment and control of such conditions relies heavily on pharmaceutical intervention using a range of antiparasitic drugs and/or their biologically active metabolites. Broad spectrum agents have been produced, although narrow and even monospecific drugs are used in some situations. Their efficacy may depend on dosage, the target pathogen(s), the host species and/or the site of infection. Optimal use of antiparasitics requires a detailed consideration of the pharmacokinetic and pharmacodynamic properties of the drugs in specific clinical contexts. This review summarizes the present status of knowledge on the metabolism, and physicochemical and pharmacological properties of the major antiparasitic drugs currently used in small animal veterinary practice. In addition, data relevant to therapeutic dosage, efficacy and clinical indication/contraindication, particularly in relation to combination drug therapy, are included.